The Transcriptional Regulator Lrp Contributes to Toxin Expression, Sporulation, and Swimming Motility in Clostridium difficile - Chen, Kuan-Yu; Rathod, Jagat; Chiu, Yi-Ching; Chen, Jenn-Wei; Tsai, Pei-Jane; Huang, I-Hsiu (Frontiers in Cellular and Infection Microbiology, 2019)
Clostridium difficile is a Gram-positive, spore-forming bacterium, and major cause of nosocomial diarrhea. Related studies have identified numerous factors that influence virulence traits such as the production of the two primary toxins, toxin A (TcdA) and toxin B (TcdB), as well as sporulation, motility, and biofilm formation. However, multiple putative transcriptional regulators are reportedly encoded in the genome, and additional factors are likely involved in virulence regulation. Although the leucine-responsive regulatory protein (Lrp) has been studied extensively in Gram-negative bacteria, little is known about its function in Gram-positive bacteria, although homologs have been identified in the genome. This study revealed that disruption of the lone lrp homolog in C. difficile decelerated growth under nutrient-limiting conditions, increased TcdA and TcdB production. Lrp was also found to negatively regulate sporulation while positively regulate swimming motility in strain R20291, but not in strain 630. The C. difficile Lrp appeared to function through transcriptional repression or activation. In addition, the lrp mutant was relatively virulent in a mouse model of infection. The results of this study collectively demonstrated that Lrp has broad regulatory function in C. difficile toxin expression, sporulation, motility, and pathogenesis.